Pelaksanaan Kunjungan Rumah Oleh Guru Bk/Konselor Di Sma Negeri Kota Padang - Wahyuni, Meri; Ilyas, Asmidir; Yusri, Yusri (Konselor, 2013)
Abtract: One of the supporting activities in BK is visiting students’ house. This activity is aimed to know, understand students condition in all aspects that have relation with family problems. Ideally, visiting students’ house must be prepared well. In fact, counseling and guidance teacher/Counselor have not prepared visiting students’ house well yet. This research is categorized into descriptive research. Research populations are all of the counseling and guidance teachers/Counselors at Senior High School in Padang city. Samples are acquired through counseling and guidance teachers/Counselors technique which the way of view is based on school’s accreditation. The result of this research showed that counseling and guidance teachers/Counselors have been able to visiting students’ house although there are still some of them found it was difficult to do.Keyword: Profile; Students Isolated